2015
DOI: 10.1007/978-3-319-03119-4_10
|View full text |Cite
|
Sign up to set email alerts
|

Plant-Microbe Association-Assisted Removal of Heavy Metals and Degradation of Polycyclic Aromatic Hydrocarbons

Abstract: Contamination by polycyclic aromatic hydrocarbons and heavy metals is a rather serious problem across the world and poses a major threat to living organisms. These are considered to be carcinogens and are constituents of oil sludge. The magnitude of PAHs released into the environment has increased drastically in recent times. This is mostly due to petroleum waste or seepage during transportation of crude oil. There have been several instances of oil spills on the coasts of India and elsewhere. In northeast Ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The functions of most of the enzymes in α-linolenic acid metabolism and the long-chain alkane biosynthesis have been reported [7, 9, 32, 33]. However, limited research was done on the PAH degradation pathway [34]. The up- and down-regulated genes in MeJA biosynthesis of blooming flowers are summarized in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…The functions of most of the enzymes in α-linolenic acid metabolism and the long-chain alkane biosynthesis have been reported [7, 9, 32, 33]. However, limited research was done on the PAH degradation pathway [34]. The up- and down-regulated genes in MeJA biosynthesis of blooming flowers are summarized in Tables 1 and 2.…”
Section: Discussionmentioning
confidence: 99%
“…Some microorganisms can reduce metal ions such as Hg 2+ and Ag + to Hg 0 and Ag 0 and provide a perfect model for total metal removal from the soil [63]. It has been experimentally demonstrated that some rhizobacteria produce extracellular enzymes such as peroxidases, reductases, Cytochome P 450 , lacases and glutathione-S-transferase, having important roles in polycyclic aromatic hydrocarbon degradation, molecules present in crude oil and known for their toxicity and carcinogenicity [64]. Meliani [65] produced a detailed review about PGPR application in soil decontamination, focusing on the genus Pseudomonas, and some of the most important strategies used by PGPR in bioremediation such as the production of biosurfactants, biofilms, toxic metal solubilization and siderophore production.…”
Section: Plant Growth-promoting Rhizobacteria a Potential Approach Fo...mentioning
confidence: 99%
“…Therefore, the rational use of organic fertilizers helps to keep the soil healthy [33,34]. Furthermore, Sarma et al [35] focus on the various case studies where plant-microbe association has been used to assist the bioremediation process of PAHs and heavy metals in oil-contaminated soil. In contrast to the research of Sarma et al, the novelty of this present study is that the mechanisms of plant and microbial remediation of PAHS-contaminated soil under different conditions are discussed further.…”
Section: Status Of Pahs Pollution In the Soil Environmentmentioning
confidence: 99%